Patients with severe mental illness and the ethical challenges related to confidentiality during family involvement: A scoping review - Hem, Marit Helene; Molewijk, Bert; Weimand, Bente; Pedersen, Reidar (Frontiers in Public Health, 2023)
Background: Despite evidence on the significant potential value of family involvement for the treatment of patients with severe mental illness, research shows that family involvement is largely underused. The duty of confidentiality is reported to be a key barrier. To develop more insight into this barrier, this scoping review focuses on the following question: What are the reported ethical challenges related to confidentiality when involving family in the treatment of patients with severe mental illness? Methods: A systematic search into primary studies was conducted in the following databases: Medline (Ovid), PsycInfo (Ovid), CINAHL (EBSCO) and Web of Science core collection (Clarivate) using a PICO scheme, and a qualitative content analysis to make the ethical challenges more explicit. Results: Twelve studies – both qualitative and quantitative - were included. We identified the following main categories of ethical challenges: 1) The best interest of family members versus confidentiality, 2) The patient’s best interest versus the right to confidentiality, 3) Patient trust and alliance as a reason not to involve the relatives or not to share information, and 4) Using confidentiality as a smokescreen. We also identified several subcategories and illustrative and concrete examples of the ethical/moral challenges. Conclusions: When looking more systematic and careful we found various types of ethical challenges related to confidentiality when involving family in the treatment of patients with severe mental illness. However, research on these ethical/moral challenges and the constituents of these challenges is still limited and often implicit. An ethical analysis creates new and thorough knowledge which may facilitate a more balanced and nuanced approach to respecting the principle of confidentiality at the one hand and considering the other moral principles as well. The duty of confidentiality does not always have to be a major barrier to family involvement. This insight and using this ethical analysis in the training of health care professionals, may benefit the patient, the family, and the services.